Correlation between clinical fetal head station and sonographic angle of progression during the second stage of labor. (2nd November 2018) - Perlman, Sharon; Kivilevitch, Zvi; Moran, Orit; Katorza, Eldad; Kees, Salim; Achiron, Reuven; Gilboa, Yinon
Abstract: Purpose: To investigate the correlation between the angle of progression and the clinical fetal head station (FHS) during the second stage of labor, and to build reference range. Materials and methods: A prospective, observational study was conducted. Women carrying singleton term pregnancies were enrolled during the second stage of labor. FHS was assessed manually by a senior obstetrician, while the angle of progression (AOP) was assessed by transperineal ultrasound (TPU). Both examiners were blinded to each others results. The correlation between the sonographic AOP and the clinical FHS was analyzed. Results: Seventy patients comprised the study group. Clinical FHS demonstrated an excellent correlation with the sonographic measurement of AOP (Pearson's Correlation 0.642, p < 0.001). This correlation was best described by a cubic regression according to the formula: 123.800 + 10.290 × FHS −2.889 * FHS +0.910, (r 2 = 0.423, p < .001). After aggregation of the mean AOP per FHS, the relative predicted centiles values and standard deviation were calculated. The mean Z score between measured and predicted values of the AOP for a given FHS was 0.007 (range −0.13 to +0.006). Conclusions: Our results demonstrate a significant correlation between the clinical FHS and the TPU measured AOP. These standardized sonographic values may serve the obstetrician as a reliable, objective auxiliary tool for the evaluation of the FHS during the second stage of labor.